Optimization of Squeeze Cementing Using Ultrafine Cement in Tight Talang Akar Formation, Ramba Field - Ayi Yanuardi; KRT Nur Suhascaryo; Dyah Rini Ratnaningsih (Journal of Petroleum and Geothermal Technology, 2026)
Ramba Field, Pertamina Hulu Rokan Zone 4 is located in South Sumatera, Indonesia. There are secondary cementing problems due to the tight injectivity rate. The failure caused a loss of time and a loss of production opportunity. This paper aims to demonstrate the successful application of ultrafine cement in rejuvenating a brownfield site in South Sumatera by effectively shutting off water channels. The approach involved a thorough reservoir analysis to identify water producing zones and optimize well placement. Ultrafine cement was then precisely placed using advanced cementing techniques, targeting water channels and permeable zones. Reservoir characteristics in the Talang Akar Formation have a good permeability and a normal injectivity rate, but when using conventional slurry, it was difficult to inject into the reservoir. Ultrafine cement material has a smaller particle size than conventional cement, which gives it the penetration ability to seal thief channel behind the casing and even the pore throat. The application of ultrafine cement led to a substantial reduction in water production, resulting in improved well productivity and enhanced sustainability of reservoir operations. The cement bond data result showed improved amplitude that could not be achieved by conventional Class G oil well cement and brought effect to decreasing water cut result. Ultrafine Cement with finer grain material (3-5 micron)/1000 Mesh compared to normal API Class G Cement around 325 Mesh resulting Low permeability slurry and rapid compressive strength that able to penetrate tiny channel behind casing. It was effective to improve cement bond in microchannel and restrict fluid flow in unwanted zone resulting Good CBL (<10 mV). This method can keep the production up to true reservoir production performance while minimizing water management issues and repetitive squeeze cement job and reduce rig cost. This paper contributes novel insights by showcasing the successful utilization of ultrafine cement for water shut-off in brownfield rejuvenation efforts. By emphasizing the link between effective water management and sustainable well production, it adds valuable knowledge to the petroleum industry's quest for environmentally conscious and economically viable reservoir management practices that are applicable to tight reservoirs around the world.